Assessment of Surface Energy Fluxes variation with Land Cover Parameters using LandSat Satellite data - Bala R.; Yadav V.P.; Kumar D.N.; Prasad R. (My University, 2025)
The urban heat island (UHI) is formed due to higher local temperatures in urban areas than surrounding rural areas. Impervious surfaces and vegetation are the two major land covers that have the capability to modify energy fluxes. The Latent Heat flux, Sensible Heat Flux and the Ground Heat flux was obtained for Bangalore city and ratio of fluxes to net radiation was calculated. The mean of ratio of each flux to net radiation was calculated for each land cover and found that the urban and bare soil region shows higher values of G/Rn as compared to the vegetated land covers. The urban land cover showed higher values of H/Rn as compared to the natural land covers and the vegetation and waterbody showed higher values of LE/Rn than other land covers. The relation of sensible heat flux with imperviousness and latent heat flux with vegetation was determined. The plot of H/Rn with ISF and LE/Rn with NDVI, both showed good positive relation. © 2022 International Radio Science Union (URSI).